Identification and causal assessment of supply chain flexibility. Issue 2 (19th September 2019) - Singh, Rohit Kr; Modgil, Sachin; Acharya, Padmanav
Abstract : Purpose: The purpose of this paper is to map the causal relations among various supply chain flexibility (SCF) dimensions having significant impact on the Indian personal hygiene industry. Design/methodology/approach: The author(s) have gone through extensive literature review and extracted 22 SCF dimensions. After conducting field visits and expert interaction in the firm related to case industry, 11 major SCF dimensions that seem to have a significant amount of influence on supply chain performance of the firms were retained for further consideration. The author(s) have used decision making trial and evaluation laboratory (DEMATEL) to establish initial causality and structural equation model (SEM) to investigate the contribution of different flexibility dimensions on overall SCF. Findings: After DEMATEL analysis, three major SCF dimensions were considered for SEM modeling. The result shows that product flexibility and physical distribution flexibility have favorable influence on the SCF, while the demand management flexibility adversely impacts overall SCF. Practical implications: The approach adopted in the study can help firms to determine and exercise the flexibility dimensions of a particular supply chain. The DEMATEL and SEM offer a facilitation to explain the causal relationship between the different dimensions to take long-term decisions and address the uncertainty in the demand and supply side. Originality/value: This paper has made an attempt to evaluate the supply chain flexibilities, prioritize them and evaluate the relationship amongst these flexibilities and the degree to which they affect or are affected by one another in the Indian personal hygiene industry.